SYSTEMATIC LITERATURE REVIEW : RIWAYAT PENYAKIT INFEKSI DAN STUNTING PADA BALITA - Rochmawati (Institut Kesehatan dan Teknologi Al Insyirah, 2025)
Systematic literature review to analyze the relationship BETWEEN history of infectious diseases AND stunting in toddlers based on the latest scientific evidence. The research methodology used the PRISMA 2020 approach with a systematic search of electronic databases including PubMed/MEDLINE, Scopus, Web of Science, CINAHL, and Google Scholar for the period 2020-2024. Of the 309 articles identified, 15 articles met the inclusion criteria for the final analysis. The synthesis results showed that children with a history of recurrent infections were at 2.8-3.2 times higher risk of stunting than children without a history of infection. The most influential infections include diarrhea and acute respiratory infections (ARI). The underlying biological mechanisms involve malabsorption of nutrients, increased metabolic needs, and decreased food intake. Comprehensive infection prevention and control programs have been shown to reduce the prevalence of stunting by up to 15% within two years. Factors that influence this relationship include socioeconomic status, access to health services, and nutritional status. This review underlines the importance of integrating infection control programs into stunting prevention strategies.